FORMATION OF MODERN YOUTH MOVEMENT IN UKRAINE - Тімкін, І. Ф. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is devoted to the problems of formation of youth civic activity in the context of sociаl and political processes, consideration of the youth movement development stages in Ukraine, determination of the peculiarities of its manifestation in the eastern regions of the country